Elaboration and validation of a primer about care for premature babies in the hospital discharge process (Research, Society and Development, 2021)
Objective: to build and validate an illustrated educational booklet for family members about care for the premature baby in the discharge process from the Neonatal Intensive Care Unit. Methodology: the participants in this qualitative, methodological study were thirteen experts and twenty responsible of babies or children up to one year of age, using online forms. A Likert scale and the Content Validity Index were used to evaluate and validate, respectively. Approved by the Research Ethics Committee. Results: the data were organized in: preparation of booklet; and, validation and adequacy of the educational manual with expert judges and target audience. The knowledge and suggestions of each audience were essential to make the themes proposed in the booklet legitimate and effective. Conclusion: an educational booklet was built and validated, achieving satisfactory rates. The material contains orientations that will help health education.